The Mediating Role of Organizational Commitment in the Influence of Workload and Emotional Exhaustion on Employee Performance - Ratri, Lintang Mutiara; Swasti, Ika Korika; Rosyanti, Daisy Marthina (UNIVERSITAS PAKUAN, 2025)
Along with the increasing global population and the rising prevalence of diseases, the demand for healthcare professionals continues to grow. A shortage of healthcare workers, limited healthcare budgets, as well as issues related to quality and safety have led to the need for initiatives to redesign the healthcare workforce. The purpose of this study is to examine how workload and emotional exhaustion affect employee performance among staff at the Utama Community Health Center in Semanding District. This study also investigates the mediating role of organizational commitment. The research employs the Partial Least Squares (PLS) method, which has the capability to examine relationships between variables. The sampling technique used is a saturated sample, consisting of 73 respondents. The results of this study indicate that workload has a negative and significant effect on employee performance; emotional exhaustion also has a negative and significant effect on employee performance; workload has a negative and significant effect on employee performance through the mediating role of organizational commitment; and emotional exhaustion has a negative and significant effect on employee performance through the mediating role of organizational commitment among staff at the Utama Community Health Center in Semanding District.